Exploration of the pathogenesis of nephrotic syndrome and traditional Chinese medicine intervention based on gut microbiota - Li, Jing; Xu, Yupei; Sun, Tianhao; Zhang, Xiaotian; Liang, Huimin; Lin, Wei; Yu, Hangxing; Yang, Bo; Yang, Hongtao (Frontiers in Immunology, 2024)
Nephrotic syndrome (NS) represents a prevalent syndrome among various chronic kidney disease pathologies and is known for its higher severity and worse prognosis compared with chronic glomerulonephritis. Understanding its pathogenesis and identifying more effective treatment modalities have long been a concern of kidney specialists. With the introduction of the gut–kidney axis concept and the progress in omics technologies, alterations in the gut microbiota have been observed in primary and secondary NS. This link has been extensively researched in conditions such as diabetic nephropathy and immunoglobulin A (IgA) nephropathy. Thus, dysbiosis of the gut microbiota is seen as a crucial contributing factor in NS; however, there is a lack of comprehensive reviews that elucidate the changes in the gut microbiota across different NS conditions and that describe its mechanistic role in the disease. Moreover, serving as an innate regulator of the gut microbiota, traditional Chinese medicine (TCM) has the potential to exert a profound impact on the expression of inflammation-promoting agents, decreasing the levels of endotoxins and uremic toxins. In addition, it strengthens the stability of the intestinal barrier while controlling the metabolic function of the body through its efficient modulation of the gut microbiota. This intricate process yields far-reaching consequences for NS.